2018
DOI: 10.1016/j.ijsu.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of goal-directed fluid therapy on early cognitive function in elderly patients with spinal stenosis: A Case-Control Study

Abstract: GDFT can maintain the stability of perioperative hemodynamics in the prone position of elderly patients with spinal stenosis, improve the balance between perfusion of tissue and organ and supply and demand of oxygen, reduce the inflammatory response, and reduce the incidence of early POCD in this type of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This reduces the risk of excessive fluid administration. Whereas an earlier observational study reported a 75% reduction in postoperative delirium incidence with goal-directed fluid therapy in spinal surgery, 131 a recent clinical trial has reported no significant difference. 132 It is, however, worth noting that both studies have small patient size and likely lack statistical power.…”
Section: Intravenous Fluid and Blood Products Administrationmentioning
confidence: 89%
“…This reduces the risk of excessive fluid administration. Whereas an earlier observational study reported a 75% reduction in postoperative delirium incidence with goal-directed fluid therapy in spinal surgery, 131 a recent clinical trial has reported no significant difference. 132 It is, however, worth noting that both studies have small patient size and likely lack statistical power.…”
Section: Intravenous Fluid and Blood Products Administrationmentioning
confidence: 89%
“…18 Additionally, it has been recently suggested that more efficient maintenance of normocapnia and cardiac blood flow (by applying a goal directed fluid therapy strategy) might also decrease postoperative cognitive impairment in elderly patients undergoing noncardiac surgery. 4,19 We hypothesized that a closed-loop management of (1) anesthetic depth (via processed EEG monitoring), (2) cardiac blood flow (via stroke volume optimization), and (3) lung ventilation (via optimization of tidal volume and respiratory frequency to maintain predefined end-tidal carbon dioxide [ETco 2 ] targets) using three independent controllers would outperform manual control of these variables, and as a result, patients would present with less postoperative neurocognitive impairment compared to patients having standard, manually adjusted anesthesia.…”
Section: Editor's Perspectivementioning
confidence: 99%
“…Published literature describing the use of GDFT in spine surgeries is limited ( 6 , 13 , 53 , 54 ). Dynamic indices such as pulse pressure variation, stroke volume variation, corrected flow time, and plethysmography index variability have been commonly used to predict fluid responsiveness among GDFT trials ( Table 1 ) ( 33 , 34 , 55 , 56 ).…”
Section: Physiologic Changes During Prone Positioningmentioning
confidence: 99%
“…Dynamic indices such as pulse pressure variation, stroke volume variation, corrected flow time, and plethysmography index variability have been commonly used to predict fluid responsiveness among GDFT trials ( Table 1 ) ( 33 , 34 , 55 , 56 ). Significant reduction in blood loss and blood transfusion, fewer post-operative respiratory complications, faster return of bowel function after surgery, shorter length of stay, reduced number, and duration of hypotensive episodes, and decreased incidence of nausea, vomiting and post-operative delirium have been reported with the use of GDFT in patients undergoing spine surgeries ( 6 , 13 , 53 ). The last finding is attributed to a reduction of peripheral inflammatory markers IL-6 and S100β and becomes of particular interest as fluid balance has been described as a modifiable risk factor of post-operative delirium in this patient setting ( 14 ).…”
Section: Physiologic Changes During Prone Positioningmentioning
confidence: 99%